Scientists’ perception of ethical issues in nanomedicine - a case study - Costa, HS (2011)
Research and development in nanomedicine has been accompanied by the consideration of ethical issues; however, little is known about how researchers working in this area perceive such issues. Extracting data from 22 semi-structured interviews with nanomedicine practitioners, this case study explores scientists’ attitude towards and knowledge of ethical issues. We found that scientists reflect with ambiguity on the reputed novelty of nanomedicine and what are ethical issues and risks in their work. Respondents see no necessity for a paradigm shift in ethical considerations, but view ethical issues in nanomedicine as overlapping with those of other areas of biomedical research. Most respondents discuss ethical issues they faced in scientific work with their colleagues but expect benefit from additional information and training on ethics. Our findings can contribute to the design of new strategies - including training programs - to engage scientists in ethical discussion and stimulate their responsibility as nanomedicine practitioners.